2015
DOI: 10.1088/1674-1056/24/5/058904
|View full text |Cite
|
Sign up to set email alerts
|

Identifying influential nodes based on graph signal processing in complex networks

Abstract: Identifying influential nodes in complex networks is of both theoretical and practical importance. Existing methods identify influential nodes based on their positions in the network and assume that the nodes are homogeneous. However, node heterogeneity (i.e., different attributes such as interest, energy, age, and so on) ubiquitously exists and needs to be taken into consideration. In this paper, we conduct an investigation into node attributes and propose a graph signal processing based centrality (GSPC) met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Zhao et al (2015) suggested the comprehensive consideration of the influence of node characteristics and nodes that are heterogeneous to network topologies. The mining of important nodes is conducted through synthetic evaluation and merging, main eigenvector calculations with a graphical Fourier transform and heterogeneous node integration through graph signal-processing-based centrality.…”
Section: Graph-theoretic Node Importance Mining On Network Topologiesmentioning
confidence: 99%
“…Zhao et al (2015) suggested the comprehensive consideration of the influence of node characteristics and nodes that are heterogeneous to network topologies. The mining of important nodes is conducted through synthetic evaluation and merging, main eigenvector calculations with a graphical Fourier transform and heterogeneous node integration through graph signal-processing-based centrality.…”
Section: Graph-theoretic Node Importance Mining On Network Topologiesmentioning
confidence: 99%
“…For example, efficient methods for spreading information positively can be employed in warning information spreading in emergency training or realistic emergency scenes. Considerable research has been performed to improve spreading efficiency, such as the shortest spreading paths [1][2][3][4], spreading strategies [5][6][7][8], influential spreader [9][10][11][12][13][14], spreading process [15][16][17][18][19] and spreading behaviours [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their huge utility, how to identify important nodes in complex networks has been a wide concern. [1][2][3] Methods of ranking nodes in complex networks usually use the topological properties of nodes to judge their importance. Commonly, these ranking methods are divided into a single-index ranking method (SRM) and multiple-index ranking method (MRM).…”
Section: Introductionmentioning
confidence: 99%